The clinical prospects and challenges of photothermal nanomaterials in myocardium recovery after myocardial infarction - Yang, Jiali; He, Jian; Yue, Tian; Pei, Haifeng; Xiong, Shiqiang; Tang, Yue; Hou, Jun (Frontiers in Bioengineering and Biotechnology, 2024)
The high morbidity and mortality rates associated with myocardial infarction pose a serious threat to human health. Early diagnosis and appropriate treatment are crucial in saving the lives of patients. In recent years, nanomaterials-based technologies have played a significant role in developing new strategies for cardiac repair, particularly in the use of photothermal nanomaterials, which show great potential in treating myocardial infarction. This review aims to describe the characteristics of photothermal nanomaterials, their effects on cardiomyocyte proliferation and angiogenesis, and the mechanism of cardiac tissue repair. This review serves as a valuable reference for the application of photothermal nanomaterials in the treatment of myocardial infarction, with the ultimate goal of expediting the translation of these treatment strategies into clinical practice.